2018
DOI: 10.5194/amt-11-2135-2018
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of ozone profiles from OMPS limb scattering observations

Abstract: Abstract. This study describes a retrieval algorithm developed at the University of Bremen to obtain vertical profiles of ozone from limb observations performed by the Ozone Mapper and Profiler Suite (OMPS). This algorithm is based on the technique originally developed for use with data from the SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY (SCIAMACHY) instrument. As both instruments make limb measurements of the scattered solar radiation in the ultraviolet (UV) and visible (Vis) spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 37 publications
2
53
0
Order By: Relevance
“…The QBO is a quasi-periodic variation of the tropical wind direction in the tropical stratosphere: easterly and westerly wind regimes propagate downward with a variable period of approximately 28 months at a given altitude level. Even though it is a tropical phenomenon, the effects of this variable wind pattern on ozone are not confined to the tropical region: they extend to mid and high latitudes and are associated with the secondary meridional circulation (Baldwin et al, 2001). illustrated the effects of the QBO on ozone profiles as a function of altitude with two peaks in ozone changes found at 20-27 km and at 30-38 km, showing opposite phases in the tropics and being in phase at mid latitudes.…”
Section: Multivariate Linear Regression Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…The QBO is a quasi-periodic variation of the tropical wind direction in the tropical stratosphere: easterly and westerly wind regimes propagate downward with a variable period of approximately 28 months at a given altitude level. Even though it is a tropical phenomenon, the effects of this variable wind pattern on ozone are not confined to the tropical region: they extend to mid and high latitudes and are associated with the secondary meridional circulation (Baldwin et al, 2001). illustrated the effects of the QBO on ozone profiles as a function of altitude with two peaks in ozone changes found at 20-27 km and at 30-38 km, showing opposite phases in the tropics and being in phase at mid latitudes.…”
Section: Multivariate Linear Regression Termsmentioning
confidence: 99%
“…For more details about the University of Bremen OMPS-LP retrieval algorithm implementation and validation, readers are referred to Arosio et al (2018), and for a description of SCIAMACHY retrieval and the validation of the ozone profiles, to Jia et al (2015). Briefly, in Arosio et al (2018) it has been shown that the retrieved OMPS-LP profiles averaged on a yearly basis agree with MLS within 5 %-10 % between 20 and 50 km, while below 20 km discrepancies are larger, especially in the tropical upper troposphere and lower stratosphere. Also, the validation with ozonesondes showed an agreement within ±7 % between 20 and 30 km in five chosen latitude bands, with a larger overestimation of the retrieved profiles in the tropics below 22 km.…”
Section: Instruments and Data Setsmentioning
confidence: 99%
“…The atmospheric modelling community is particularly interested in this type of information because climate models require information about stratospheric aerosol to define the initial conditions and/or to assess the accuracy of their performance (Solomon et al, 2011;Fyfe et al, 2013;Brühl et al, 2015;Bingen et al, 2017). Other important applications of stratospheric aerosol data are the investigation of the effects of geoengineering (IPCC, 2013;Kremser et al, 2016) and use of stratospheric aerosol information to improve the retrieval of stratospheric trace gases, e.g., water vapour (Rozanov et al, 2011) and ozone (Arosio et al, 2018;Zawada et al, 2018), from remote-sensing instruments. Most commonly, stratospheric aerosols are characterized by either their extinction coefficient (Ext) or one or several particle size distribution (PSD) parameters (e.g., median (r med ), effective (r eff ) or mode (R mod ) radius, distribution width parameter (σ ), aerosol particle number density (N)).…”
Section: Introductionmentioning
confidence: 99%
“…Within linear theory and the assumption in force that the better resolved data set contains no sizeable amount of a priori information, the Connor et al approach indeed solves the problem that the original datasets are not directly comparable due to different vertical resolutions. The problem of interpolability of averaging kernels is discussed in Arosio et al (2018). 30 Problems occur when linear theory is no longer adequate to describe the problem.…”
mentioning
confidence: 99%